Management of traumatic wounds in the Emergency Department: position paper from the Academy of Emergency Medicine and Care (AcEMC) and the World Society of Emergency Surgery (WSES). Issue 1 (December 2016) - Prevaldi, Carolina; Paolillo, Ciro; Locatelli, Carlo; Ricci, Giorgio; Catena, Fausto; Ansaloni, Luca; Cervellin, Gianfranco
Abstract Traumatic wounds are one of the most common problems leading people to the Emergency Department (ED), accounting for approximately 5, 4 % of all the visits, and up to 24 % of all the medical lawsuits. In order to provide a standardized method for wound management in the ED, we have organized a workshop, involving several Italian and European experts. Later, all the discussed statements have been submitted for external validation to a multidisciplinary expert team, based on the so called Delphi method. Eight main statements have been established, each of them comprising different issues, covering the fields of wound classification, infectious risk stratification, tetanus and rabies prophylaxis, wound cleansing, pain management, and suture. Here we present the results of this work, shared by the Academy of Emergency Medicine and Care (AcEMC), and the World Society of Emergency Surgery (WSES).